Triarchic Model of Psychopathy and Intimate Partner Violence: An Empirical Study on the Italian Community - Sica, Claudio (Journal of interpersonal violence, 2024)
Intimate partner violence (IPV) is a serious and recurrent phenomenon in many societies with severe physical and psychological consequences. In the present study, we aimed to explore the role of triarchic dimensions of psychopathy (disinhibition, boldness, and meanness) across gender in this occurrence. A questionnaire on inflicted (self) and experienced (partner) IPV and the Triarchic Psychopathy Measure were administered to a sample of 1,149 individuals from the Italian community. In general, self and partner IPV were moderately correlated. Bayesian regression analysis showed that disinhibition was positively correlated to both self and partner IPV (psychological and physical). In addition, boldness was negatively associated with perpetrated psychological IPV. Interactions by gender showed that meanness was positively related to perpetrated IPV in women (psychological and physical), whereas men with disinhibition features inflicted more physical violence than women. A high externalizing tendency (i.e., disinhibition) is therefore an important correlate of both perpetrated and reported IPV; moreover, boldness was associated with less psychological violence in general, whereas the effect of meanness depended on the gender of the individuals involved. Interestingly, the association between IPV and self-reported delinquent activities was low in magnitude (Spearman’s Rho around .20) suggesting limited overlap between these two constructs.